2013
DOI: 10.1002/anie.201307371
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Silver Phosphate Catalyzed Transformation of ortho‐Alkynylaryl Ketones into 1H‐Isochromene Derivatives through an Intramolecular‐Cyclization/Enantioselective‐Reduction Sequence

Abstract: The transformation of ortho-alkynylaryl ketones through a cyclization/enantioselective-reduction sequence in the presence of a chiral silver phosphate catalyst afforded 1H-isochromene derivatives in high yield with fairly good to high enantioselectivity. An asymmetric synthesis of the 9-oxabicyclo[3.3.1]nona-2,6-diene framework, which has been found in some biologically active molecules, is presented as a demonstration of the synthetic utility of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(36 citation statements)
references
References 83 publications
1
35
0
Order By: Relevance
“…294 In recent years, chiral counterion-induced enantioselective transformations, i.e., asymmetric counterion-directed catalysis (ACDC) have emerged as powerful tools in asymmetric synthesis. 296 This reaction proceeded through a tandem cyclization/enantioselective-reduction reaction pathway with a chiral silver phosphate catalyst 407 as well as a Hantzsch ester 408 as the reductant. 296 This reaction proceeded through a tandem cyclization/enantioselective-reduction reaction pathway with a chiral silver phosphate catalyst 407 as well as a Hantzsch ester 408 as the reductant.…”
Section: Carbonyl-yne Cycloisomerizationmentioning
confidence: 99%
“…294 In recent years, chiral counterion-induced enantioselective transformations, i.e., asymmetric counterion-directed catalysis (ACDC) have emerged as powerful tools in asymmetric synthesis. 296 This reaction proceeded through a tandem cyclization/enantioselective-reduction reaction pathway with a chiral silver phosphate catalyst 407 as well as a Hantzsch ester 408 as the reductant. 296 This reaction proceeded through a tandem cyclization/enantioselective-reduction reaction pathway with a chiral silver phosphate catalyst 407 as well as a Hantzsch ester 408 as the reductant.…”
Section: Carbonyl-yne Cycloisomerizationmentioning
confidence: 99%
“…(4‐Methoxyphenyl)[2‐(phenylethynyl)phenyl]methanone (1): Yellow oil (463.5 mg, 99 %). IR (neat) ν̃ = 2940, 1651, 1580, 1412, 1330, 1122 cm –1 .…”
Section: Methodsmentioning
confidence: 99%
“…7 Subsequently, Terada and Floreancig showed that phosphoric acid catalysts can also be used to catalytically generate chiral oxocarbenium ion electrophiles, which undergo enantioselective attack by hydride or allyl nucleophiles, respectively. 8 In a distinct strategy, Schaus has demonstrated the complementary approach of catalytic generation of a chiral nucleophile via tartarate-derived diol-catalysis of vinyl and aryl boronate esters. 9 Rueping, Lou and Liu, and Cozzi have also shown that chiral enamine nucleophiles, catalytically generated from amine catalysts and aldehydes, add to oxocarbenium ions with high enantioselectivities.…”
Section: Introductionmentioning
confidence: 99%